2021
DOI: 10.5194/acp-2021-626
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measurement report: Molecular characteristics of cloud water in southern China and insights into aqueous-phase processes from Fourier Transform Ion Cyclotron Resonance Mass Spectrometry

Abstract: Abstract. Characterizing the molecular composition of cloud water could provide unique insight into the aqueous chemistry. Field measurement was conducted at Mt. Tianjing in southern China during May, 2018. Thousands of formulas (C5-30H4-55O1-15N0-2S0-2) were identified in cloud water by Fourier transform-ion cyclotron resonance mass spectrometry (FT-ICR MS). CHON represents the dominant component (43.6–65.3 % of relative abundance), followed by CHO (13.8–52.1 %). S-containing formulas constitute the remaining… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 71 publications
1
3
0
Order By: Relevance
“…Rainwater and PM 2.5 samples contained high proportions of nitrogen‐containing formulas (Figures 5a and 5b; Figure S7 in Supporting Information ). The case of high proportion of nitrogen‐containing compounds was similar to recent report about DOM compositions of cloud water and PM 2.5 collected in Tianjing (China) (Sun et al., 2021). Moreover, the authors suggested that nitrogen‐containing compounds can be largely generated via in‐cloud processes.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Rainwater and PM 2.5 samples contained high proportions of nitrogen‐containing formulas (Figures 5a and 5b; Figure S7 in Supporting Information ). The case of high proportion of nitrogen‐containing compounds was similar to recent report about DOM compositions of cloud water and PM 2.5 collected in Tianjing (China) (Sun et al., 2021). Moreover, the authors suggested that nitrogen‐containing compounds can be largely generated via in‐cloud processes.…”
Section: Resultssupporting
confidence: 89%
“…The comparison among the samples is expected to have the same bias. Accordingly, the results are still meaningful and can represent a possible relationship among sources (Altieri et al., 2016; Sun et al., 2021). In this study, DOM (/WSOM) derived from rainwater and WICs was compositionally highly similar to those derived from fine aerosol particles.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, cloud water samples with high probability of smoke influence showed significantly higher concentrations compared to samples with a low probability of smoke influence for K + , SO 4 2− , NH 4 + , and TOC, all of which have been previously identified in cloud water influenced by biomass burning events (Budhavant et al., 2014; Stahl et al., 2021). Previous wildfire influenced cloud water studies have suggested that the TOC composition may contain carbonyls, carboxylic acids, nitrogen‐containing compounds, oligomeric species, and light absorbing secondary organic aerosols formed within clouds (Cook et al., 2017; Li et al., 2020; Schurman et al., 2018; Sun et al., 2021; Tomaz et al., 2018). These results suggest long‐range transported smoke frequently alters the chemical composition of cloud water at Whiteface Mountain.…”
Section: Discussionmentioning
confidence: 99%
“…Within cloud droplets, aqueous reactions can occur and alter cloud droplet chemical composition (Blando & Turpin, 2000; Ervens et al., 2011; Sun et al., 2021). For example, components of biomass burning aerosols (e.g., levoglucosan, catechol, aminophenol) can react with aqueous hydroxyl radicals to form cloud processing tracers, such as oxalate, malonate, and mesoxalate (Tomaz et al., 2018).…”
Section: Introductionmentioning
confidence: 99%